2003
DOI: 10.1163/156856203322274969
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-coated textile scaffolds as candidate in liver tissue engineering: II. Evaluation of spheroid formation and viability of hepatocytes

Abstract: In this study we evaluate the performance of primary rat hepatocytes and HepG2 cells on chitosan-collagen hydrogel-coated textile scaffolds. Light microscopy and electron microscopic observations showed attachment and aggregate formation tendency of hepatocytes on the scaffolds. As tested by the tetrazolium reduction (MTT) assay it was evident that cells had preserved mitochondrial functionality. It was also observed that pure collagen and collagen blended scaffolds allowed higher cell growth than pure chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Our observations indicated that nitrocellulose membranes supported HepG2 cell attachment, morphology, proliferation, and function, which were similar to the results reported in other studies (Kataoka et al 2005;Risbud et al 2003;Kasoju et al 2009;She et al 2008), suggesting that we should further explore the application of nitrocellulose membranes in membrane bioreactors. Recently, several new membrane materials have been used in bioreactors, such as cuprophane, cellulose acetate, polysulfone, and polypropylene membranes.…”
Section: Discussionsupporting
confidence: 90%
“…Our observations indicated that nitrocellulose membranes supported HepG2 cell attachment, morphology, proliferation, and function, which were similar to the results reported in other studies (Kataoka et al 2005;Risbud et al 2003;Kasoju et al 2009;She et al 2008), suggesting that we should further explore the application of nitrocellulose membranes in membrane bioreactors. Recently, several new membrane materials have been used in bioreactors, such as cuprophane, cellulose acetate, polysulfone, and polypropylene membranes.…”
Section: Discussionsupporting
confidence: 90%
“…[41][42][43][44][45][46][47][48][49] Because of their unique properties, hydrogels have been explored for a wide range of biomedical applications, including drug delivery, 50 protein delivery, 51 gene delivery, 52 wound dressing, 53 water elimination for edema, 54 cosmetic reconstruction, 55 contact lenses, 56 and tissue engineering. 49,[57][58][59] One major challenge in employing hydrogels for load-bearing connective tissue repair in cartilage, tendon, intervertebral disk, ligament, and so on, is insufficient mechanical strength. For instance, articular cartilage contains *70% water and bears loads up to 100 MPa, 60 but most hydrogels, either synthetic or derived from natural sources, can be easily broken by pressing with a finger or pulling with the hand, indicating that they are much weaker than native cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hence for rapid hydration and regeneration of skin, aloe is intended to be used in this formulation to make the skin smooth and elastic. Though many studies have shown the incompatibility of skin fibroblasts with chitosan, it has been reported that the addition of collagen facilitates the attachment and proliferation of skin fibroblasts [34][35][36][37] .…”
Section: Fig 2: Sa-β-gal Positive Nih3t3 Mouse Fibro Blasts Cells (Cmentioning
confidence: 99%